Prevalence of cystic fibrosis mutations in the Grampian region of Scotland. Issue 4 (April 1993) - Miedzybrodzka, Z H; Dean, J C; Russell, G; Friend, J A; Kelly, K F; Haites, N E
Abstract : We have identified all known sufferers of cystic fibrosis (CF) alive in the Grampian region, north east Scotland, on 1 January 1989. DNA samples were obtained for a prevalence study of the common mutations with near to complete ascertainment. A relatively high prevalence of the delta F508 mutation was found (82%), with one of four mutations being present on 92% of CF chromosomes. The high prevalence of these four easily detectable mutations in Grampian has local implications for genetic counselling, the efficacy of population carrier screening, and the usefulness of mutation analysis in cases where the diagnosis of CF is in doubt.